Genoeses in Lima at the end of the viceroyalty - Lévano, Diego (2018)
Description of the economic dynamics of the Genoese colony settled in Lima at the end of the colonial period and deals especially with their participation in local commercial networks and overseas trade. It provides data on their status, work and jobs, economic transactions, their daily participation in the different historical processes of Peru and their adaptation and maintenance of interests in the various governments in which they lived. It addresses the search for their naturalization as neighbors by some Genoeses and the presence of the Cadiz Ligurian trade in Lima through representatives and attorneys. As a corollary, it deals with the moment of the occupation of Lima by the patriotic forces and how this affected Genoeses, either as naturalized Spaniards or as foreigners identified with the realistic cause.